Developing circular agriculture for climate change adaptation in Vietnam: Current status and challenges - Hang, Ho Thi Thuy; Sinh, Le Xuan; Phuong, Tran Trong; Nui, Nguyen Hai; Son, Cao Truong (Asian Journal of Agriculture and Rural Development, 2026)
Climate change (CC) is impacting the sustainable development of every country worldwide. To adapt to CC, the Vietnamese government has promoted circular agricultural (CA) development. This study aims to provide an overview of the current status of CA development adapted to CC in Vietnam. It reviews and evaluates international experiences in developing CA, legal regulations, and practical implementation. Data sources include scientific articles, reports from researchers, agencies, and organizations. Based on this information, a SWOT analysis was conducted to identify strengths, weaknesses, opportunities, and challenges for CA development. The results indicate that Vietnam’s CA models are prevalent at the micro and medium levels, while macro-level models are rarely deployed. CA models have demonstrated economic and environmental benefits, aiding farmers in adapting to CC. However, several challenges remain, including limited awareness among stakeholders, incomplete policy frameworks, the absence of a market for circular products, limited waste management capacity, small-scale production, and insufficient linkage in production processes. Despite these limitations, CA models are recognized as a strategic policy by the Vietnamese government to reduce greenhouse gas emissions and enhance resilience to climate change.